IMPLEMENTATION OF PROPHETIC EDUCATION IN BUILDING RELIGIOUS AND SOCIAL CULTURE AT AL FATTAH ISLAMIC HIGH SCHOOL - Sahri; Fuadi, Imam; Tanzeh, Ahmad; Kojin (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2023)
Prophetic education aims to develop noble morals and good behavior based on Islamic teachings. The implementation of prophetic education in developing religious and social power includes introducing Islamic values from an early age, providing an understanding of hadith and sunnah, and teaching social care. Prophetic education must be carried out continuously by teachers and parents so that children can understand and practice the teachings of Islam in everyday life. The type of research used is field research. The approach used in this study is a descriptive qualitative approach. Data collection techniques used with mandala interviews, observation and documentation. While in analyzing data with data condensation, display data, draw conclusions. While in analyzing data with data condensation, display data, draw conclusions. The results of the study that the efforts made by Al Fattah Islamic High School in implementing Prophetic Education Management include providing religious education integrated with the curriculum, conducting spiritual formation through religious activities and character development, and providing examples for students through the behavior of teachers